Enhanced sweet taste perception in obesity: Joint analysis of gustatory data from multiple studies - Ribeiro, Gabriela; Torres, Sandra; Fernandes, Ana B.; Camacho, Marta; Branco, Teresa L.; Martins, Sandra S.; Raimundo, Armando; Oliveira-Maia, Albino J.; , Food Reward in Bariatric Surgery Portuguese Study Group (Frontiers in Nutrition, 2022)
Introduction: While sweet taste perception is a potential determinant of feeding behavior in obesity, the supporting evidence is inconsistent and is typically associated with methodological limitations. Notably, possible associations between sweet taste perception and measures of food reward remain undetermined. Materials and Methods: We conducted a cross-sectional analysis comparing 246 individuals with severe obesity and 174 healthy volunteers using a validated method for taste perception assessment. We included gustatory variables, namely intensity and pleasantness ratings of sour, salt, sweet, and bitter tastants, and taste thresholds assessed by electrogustometry. Reward-related feeding behavior, including hedonic hunger, food addiction, feeding behavior traits, and acceptance of foods and alcohol, was evaluated using self-rated scales for comparison with gustatory measures. Results: In logistic regressions adjusted for age, gender, educational level, and research centre, we found that a greater likelihood of belonging to the obesity group was associated with higher sweet intensity ratings (OR = 1.4, P = 0.01), hedonic hunger, food addiction symptoms, restrained and emotional eating (1.7 < OR ≤ 4.6, all P ≤ 0.001), and lower alcohol acceptance (OR = 0.6, P = 0.0002). Using principal component analysis, we found that while hedonic hunger, food addiction, and emotional eating were strongly interrelated, they were not associated with sweet intensity perception that, in turn, had a closer relationship with alcohol acceptance and restrained eating. Conclusions: We found that individuals with obesity report higher sweet taste intensity ratings than healthy controls. Furthermore, while psychological measures of reward-related feeding behavior assess a common construct, sweet intensity perception may represent a different obesity-related dimension.